UMP OKU Friendly Ecosystem Policy DAMAI is launched - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 3 August 2021 - The recently launched OKU Friendly Ecosystem Policy (DAMAI UMP) is a platform for Universiti Malaysia Pahang (UMP) to share the benefits of technological expertise and extend universal brotherhood in cultivating a friendly ecosystem for disabled people (OKU) community.